Peningkatan Motorik Halus melalui Kegiatan Melipat Kertas Origami di PAUD Kober Cempaka - Elis Roslianti; Andan Firmansyah; Yuda Nugraha; Alda Nurani Asmara; Hera Maulidiyah; Hani Monika; Rini Fitriani; Sukmara Aji Falah (Jurnal Abdimas Kesehatan (JAK), 2022)
Fine motor development of a child is very important to be trained because when the fine motor development of children who are well trained will make it easier for children to carry out further developmental tasks. Usually, children will have certain motor skills at a certain age, but not every child will reach these stages at the same time. The art of origami can train children's creative abilities because of its various shapes. Playing origami can help children make their own toys, thereby creating satisfaction compared to toys that have been made or made by others. The purpose of this community service is to carry out play therapy to improve fine motor skills through origami folding activities for PAUD children at PAUD Kober, the location of this community service is in RT 07/RW 02 Sadananya Village, Sadananya District, Ciamis. This method of community service is collaborative, including writers and classroom teachers. The method chosen was to carry out play therapy on 9 students, for which we conducted education, observation, and documentation. The results of this evaluation of community service indicate that the fine motor skills of preschool children at PAUD Kober have reached indicators of success. Participants were very enthusiastic about participating in the origami folding activity. The conclusion of this community service is that play therapy activities with the origami paper folding method were carried out very well without any problems, the children were very enthusiastic, happy and in the end were able to fold origami paper neatly even though it was a little difficult at first.